A Self-management intervention to promote sufficient fruit and vegetable intake among public school teachers in Tanjay Ciy, Negros Oriental - Mira, Nona Rachel C.
Majority of recent deaths in the Philippines were attributed to noncommunicable diseases. Adequate consumption of fruits and vegetables can potentially decrease the burden of certain heart diseases and cancer. In the promotion of proper nutrition, teachers have been identified as one of the specific groups for nutrition education. Health promotion and education interventions have been shown to increase fruit and vegetable intake (FVI). Thus study evaluated the impact of a self-management intervention on psychosocial variables and FVI of pulic school teachers in Tanjay City, Negros Oriental. The psychosocial variables were derived from Bandura?s social cognitive theory andAjzen?s theory of planned behaviour. This study utilized the Solomon four-group design and self-administered questionnaires. Forty-four schools were stratified into blocks composed of four schools per block and then randomized by block to form four groups. Two of the groups were pretested while the other two groups were not pretested. One of the pretested groups and one of the unpretested groups received the self-management intervention while the other two were not exposed to the intervention. All the fourgroups were then posttested. Data collection was done between June and October 2015. A total of 228 teachers, 112 in the intervention group and 116 teachers in the control group, were included in the analysis. Nearly half (49%) of the intervention group teachers were able to attend the lecture-workshop, one of five intervention activities. Significant findings in two of four psychosocial variables, particularly diet-related attitude and knowledge regarding the recommended FVI, and a significant difference in mean FVI were only found using data of the posttest-only intervention group teachers who were able to attend the lecture-workshop and control group. There was no sufficient evidence to conclude that there was a significant difference in the FVI and psychosocial variables of the intervention and control groups post-intervention. This study also found no sufficient evidence to conclude that the effect of the self-management intervention was mediated by diet-related attitude, dietary self-efficacy, knowledge regarding the recommended FVI, and behavioural intentions related to FVI. Improvements in the design and implementation of interventions to promote adequate FVI among adults are recommended.